Mature Teratoma of the Temporal Bone in 3.5-Month-Old Baby Girl - Alshema Alqurashi; Essa Bakry; Marta Straube; Christian H. Rickert; Parwis Mir-Salim (Case Reports in Otolaryngology)
Mature teratoma is a benign germ cell tumor rarely located in the temporal bone. We are reporting a case of a mature teratoma of the temporal bone in a healthy borne 3.5-month-old baby girl with a 2-day suggestive history of otitis media and polypoidal mass expulsing from the external auditory canal of the left ear. A definitive diagnosis is made after complete excision and histological examination of the tissue. Total surgical excision of the tumor is the treatment of choice.